Klaim-Klaim Kebudayaan dalam Pemikiran Seyla Benhabib - Mudzakkir, Amin (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2016)
Whether the model of citizenship based on the national nation-state can stand in the increasingly pluralistic contemporary society might be one of the important questions at the beginning of the 21st century. Liberal thinkers are quite pessimistic on the prospect of a democratic rule of government among the states torn by ethnic, religious, identity-related differences. Issues concerning culture and religiosity are often understood within the framework of security and order. In the recent cultural contexts, Seyla Benhabib develops three normative conditions to be a model of deliberative cosmopolitan democracy, i. e., egalitarian reciprocity, voluntary self-ascription, and freedom of exit and association. With her anti-essentialism view, she defends the opinion that culture is a social construct that is mixed and plural. The term social construct is not meant to be a conjecture, but a term that has certain normative dimension to be the guideline to live through the interaction process among the autonomous human beings, including their relations with different groups. For Benhabib, the individual remains at the central position whether morally or politically, so that the groups, including the state, do not have strong justification to impose their own regulations in ways that limit the rights of a human being.